Baseline cell proliferation rates and response to UV differ in lymphoblastoid cell lines derived from healthy individuals of extreme constitution types. Issue 9 (3rd May 2021) - Chakraborty, Sumita; Singhmar, Sunanda; Singh, Dayanidhi; Maulik, Mahua; Patil, Rutuja; Agrawal, Satyam Kumar; Mishra, Anushree; Ghazi, Madeeha; Vats, Archana; Natarajan, Vivek T; Juvekar, Sanjay; Prasher, Bhavana; et al.
ABSTRACT: Differences in human phenotypes and susceptibility to complex diseases are an outcome of genetic and environmental interactions. This is evident in diseases that progress through a common set of intermediate patho-endophenotypes. Precision medicine aims to delineate molecular players for individualized and early interventions. Functional studies of lymphoblastoid cell line (LCL) model of phenotypically well-characterized healthy individuals can help deconvolute and validate these molecular mechanisms. In this study, LCLs are developed from eight healthy individuals belonging to three extreme constitution types, deep phenotyped on the basis of Ayurveda. LCLs were characterized by karyotyping and immunophenotyping. Growth characteristics and response to UV were studied in these LCLs. Significant differences in cell proliferation rates were observed between the contrasting groups such that one type ( Kapha ) proliferates significantly slower than the other two ( Vata, Pitta ). In response to UV, one of the fast growing groups ( Vata ) shows higher cell death but recovers its numbers due to an inherent higher rates of proliferation. This study reveals that baseline differences in cell proliferation could be a key to understanding the survivability of cells under UV stress. Variability in baseline cellular phenotypes not only explains the cellular basis of different constitution types but can also help set priors during the design of an individualized therapy with DNA damaging agents. This is the first study of its kind that shows variability of intermediate patho-phenotypes among healthy individuals with potential implications in precision medicine.